Recent results from CMS - Schöfbeck Robert (EPJ Web of Conferences, 2015)
The CMS experiment at the Large Hadron Collider at CERN collected a dataset of 19.5fb−1 during 8 TeV proton-proton operation. A large number of groundbreaking results were obtained from the analysis of this dataset, among them the discovery of the Higgs boson and precision measurements of important Standard Model parameters, for example the mass of the top quark. Subtle processes like the production of a Z boson by fusion of two W bosons have been measured for the first time. Moreover, many searches for physics beyond the Standard model have been carried out, both in the context of supersymmetry and beyond, which often provide tight constraints in model parameter space. This brief summary is a a short overview of the most important recent CMS results at 7 and 8 TeV.